Lenvatinib plus pembrolizumab in patients with advanced or recurrent uterine carcinosarcoma - Jonathan T. Hunt; Laura M. Chambers; Meng Yao; Amy Joehlin-Price; Robert Debernardo; Peter G. Rose (Elsevier, 2021)
Objective(s): To investigate the efficacy of pembrolizumab plus lenvatinib as a second-line or later-line therapy in women with advanced or recurrent uterine carcinosarcoma (UCS). Methods: A single-institution pharmacy database was queried for women with advanced or recurrent UCS who were prescribed concurrent pembrolizumab and lenvatinib. Patient demographic, oncologic, and immunotherapy outcomes data were recorded. Univariate analysis summarized progression-free survival (PFS) and overall survival (OS). Results: Seven patients with advanced or recurrent UCS were treated with combination pembrolizumab and lenvatinib, with a median age of 63.0 years. The majority had stage III or IV disease (n = 6, 85.7%) and had failed two or more lines of therapy (n = 7, 100.0%), and a minority were MMR deficient (n = 1, 14.3%) or PD-L1+ (n = 1, 14.3%). No partial or complete responses were observed. The median PFS was 2.6 months (95% CI, 0.9-11.2 months), and the median OS was 2.8 months (95% CI, 2.4-NE). Conclusions: In this small, retrospective series, we demonstrate that pembrolizumab and lenvatinib combination therapy may not be highly active in UCS and may be associated with similar PFS and OS as traditional cytotoxic regimens. Further study is warranted to assess the efficacy of this regimen in more targeted cohorts of women with advanced or recurrent UCS.